High resolution anatomical and functional imaging - Sanchez Panchuelo, Rosa Maria (2009)
The signal-to-noise ratio available in Magnetic Resonance Imaging (MRI)is determined by the static magnetic field strength, causing a continued drive toward higher fields to enable faster image acquisition at finer spatial resolution. The work in this thesis is primarily concerned with the development of sequences for Ultra High Field Magnetic Resonance Imaging (7T) which allow the acquisition of images with high spatial resolution for study of the structure and function of the brain.